Comparison of Biological Activity of Human Anti-Apical Membrane Antigen-1 Antibodies Induced by Natural Infection and Vaccination - Kazutoyo Miura; Hong Zhou; Samuel E. Moretz; Ababacar Diouf; Mahamadou A. Théra; Amagana Dolo; Ogobara K. Doumbo; Elissa Malkin; David Diemert; Louis H. Miller; Gregory Mullen; Carole A. Long (2008)
Abstract Vaccines represent a significant potential means of decreasing global morbidity and mortality due to malaria. Clinical trials in the United States with Plasmodium falciparum Apical Membrane Antigen 1 (AMA1) showed that the vaccine induced biologically active Abs judged by an in vitro parasite growth inhibition assay (GIA). However, the same vaccine in Malian adults did not increase biological activity, although it elevated ELISA titers. Because GIA has been used to evaluate the biological activity of Abs induced by blood stage malarial vaccine candidates, we explored this discrepancy in this study. We affinity purified AMA1-specific Abs from both U.S. vaccinees and nonvaccinated individuals living in a malaria-endemic area of Mali and performed ELISA and GIA. Both AMA1-specifc Abs induced by vaccination (U.S.) and by natural infection (Mali) have comparable biological activity in GIA when the ELISA titer is normalized. However, a fraction of Malians’ IgG that did not bind to AMA1 protein (Mali-non-AMA1 IgG) reduced the biological activity of the AMA1 Abs from U.S. vaccinees; in contrast, U.S.-non-AMA1 IgGs did not show a reduction of the biological activity. Further investigation revealed that the reduction was due to malaria-specific IgGs in the Mali-non-AMA1 IgGs. The fact that both U.S.- and Mali-AMA1-specific Abs showed comparable biological activity supports further development of AMA1-based vaccines. However, the reduction of biological activity of AMA1-specific Ab by other malaria-specific IgGs likely explains the limited effect on growth-inhibitory activity of Abs induced by AMA1 vaccination in Malian adults and may complicate efforts to develop a blood stage malaria vaccine.